If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = (4b + 1)(8b + -2) Reorder the terms: y = (1 + 4b)(8b + -2) Reorder the terms: y = (1 + 4b)(-2 + 8b) Multiply (1 + 4b) * (-2 + 8b) y = (1(-2 + 8b) + 4b * (-2 + 8b)) y = ((-2 * 1 + 8b * 1) + 4b * (-2 + 8b)) y = ((-2 + 8b) + 4b * (-2 + 8b)) y = (-2 + 8b + (-2 * 4b + 8b * 4b)) y = (-2 + 8b + (-8b + 32b2)) Combine like terms: 8b + -8b = 0 y = (-2 + 0 + 32b2) y = (-2 + 32b2) Solving y = -2 + 32b2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -2 + 32b2
| y=7x+22/3 | | -2(-3-4x)+3(2x+8)=44 | | y=-1/x-1-3 | | y-(-7)=(6/7)(x-2) | | y=-3/x-1 | | m-8=-4m+12 | | 8x^6-12x^5/2x^2 | | -15+n=1-7n | | 2(n-8/5)+41/7(-3/4n+9/10) | | -3(x-1)+2(x+3)=12 | | -2-13/8(-5/3p+1) | | -32/9(k+1/4)-11/3 | | -5/7(5/7n+11/2) | | -7(-4+v)-3(7v+7)=63 | | 1/2(a+7/6) | | x/4+11=5 | | 3w-8=34 | | -12=-4w | | 23/4v+1+5/7v | | 5r+3r=-15 | | 29/6x+17/10+x+37/8 | | 8+12=420 | | y=-8-7 | | 120=20t+(1/2)(10)t^2 | | -204=-6(6-7b) | | 21-4x=-4 | | 7x-4=20+4x | | F(x)=4x^2+8x-1 | | 20+4^3/(-8) | | 3x^2+2y^2+4xy-12=0 | | 1/2(2y)=1/2x+1/2(4) | | fuck=you |